Calculated body muscle mass as a useful screening marker for low skeletal muscle mass and sarcopenia in chronic liver disease. Issue 6 (6th March 2020) - Ichikawa, Tatsuki; Miyaaki, Hisamitsu; Miuma, Satoshi; Motoyoshi, Yasuhide; Yamashima, Mio; Yamamichi, Shinobu; Koike, Makiko; Honda, Tetsurou; Yajima, Hiroyuki; Uehara, Ryouhei; Miyazaki, Osamu; Hino, Naoyuki; et al.
Abstract : Aim: Sarcopenia is a harmful condition in patients with chronic liver disease. However, the evaluation of body muscle mass requires expensive instrumentation. The sarcopenia index (SI): (creatinine / cystatin C × 100) has been reported to correlate with muscle volume. A calculated body muscle mass (CBMM) using creatinine, cystatin C, and bodyweight also correlates with muscle mass. We evaluated the applicability of using SIs and CBMMs as screening methods for sarcopenia. Methods: Patients ( n  = 303) with liver damage were evaluated for creatinine, cystatin C, and grip strength (GS). All patients were evaluated using cross‐sectional computed tomography images of the third lumbar vertebrae to determine their skeletal muscle (SM) mass. CBMMs and SIs were compared with SMs, GSs, and sarcopenia. Results: Correlation coefficients ( R ) between SMI (SM / height 2 [m 2 ]) and CBMM, and between GS and CBMM were 0.643 and 0.723, respectively. Factors contributing to low GSs; low SM indices; and sarcopenia were age and SM; sex, age, GS, SI, and CBMM indices; and sex, bodyweight, and CBMM, respectively, in the multivariate logistic analyses. Receiver operating characteristic curve analysis between sarcopenia and CBMM showed an area under the receiver operating characteristic curve of 0.78504 in women and 0.86067 in men. Cut‐off CBMM values for sarcopenia were 27.903 (sensitivity 0.73958) in women and 39.731 (sensitivity 0.7941) in men. Conclusions: CBMMs and SIs are simple and minimally invasive screening methods in which low levels are indicative of sarcopenia in patients with liver disease.